POTENSI KOMPOS Azolla pinnata SEBAGAI ALTERNATIF PENGGUNAAN PUPUK ANORGANIK NPK UNTUK PERTUMBUHAN BIBIT KAKAO DI TANAH PODSOLIK MERAH KUNING - Suci Arlin; Sopiana Sopiana; Sarwendah Ratnawati Hermanto; Beny Setiawan; Rika Fitry (Politeknik Negeri Ketapang, 2025)
The use of inorganic fertilizers in cocoa nurseries has a negative impact on environmental sustainability, so it is necessary to optimize organic fertilizers that are proven to be environmentally friendly and can be used sustainably. Therefore, an alternative is needed to substitute organic fertilizers, namely the use of Azolla pinnata compost. Azolla pinnata compost has the potential to substitute the use of inorganic fertilizers N, P, and K because the nutrient content is already available in Azolla pinnata compost. This study aims to determine the minimum dose of Azolla pinnata compost that provides the same growth as inorganic fertilizer (NPK) in enhancing the growth of cocoa seedlings in PMK soil. This study used a non-factorial Completely Randomized Design (CRD) consisting of 5 treatment levels with 4 replications. So that 20 experimental units were obtained. Each treatment consisted of 3 plant samples so that 60 plants were obtained. The treatments consisted of K0: NPK fertilizer 24 g polybag-1, K1: Azolla pinnata compost 100 g polybag-1, K2: Azolla pinnata compost 150 g polybag-1, K3: Azolla pinnata compost 200 g polybag-1, K4: Azolla pinnata compost 250 g polybag-1. The data obtained from the research results were analyzed statistically using Analysis of Variance (ANOVA). If the treatment had a significant effect, it was continued with the Least Significant Difference (LSD) test at the 5% level using the DSAASTAT application. The results of the analysis of variance showed that the treatment of inorganic fertilizer (NPK) and Azolla pinnata compost had a significant effect on the variables of plant height, stem diameter and leaf chlorophyll. The results of the 5% LSD test showed that treatment with a dose of Azolla pinnata compost of 200 g polybag-1could provide the same growth as the administration of inorganic fertilizer (NPK) with a dose of 24 g polybag-1in cocoa seedlings in PMK soil.